Observation of fire safety provision and factors associated with knowledge, attitude and practices among hostel occupants in a public university in Malaysia - Ahmad, Alwaqfi Ahmad Saeed (2021)
Man-made fire particularly in the multi-dwelling building such as hostel remains to be one of the top priorities in emergency preparedness. Failure to prepare adequately may results in extensive losses not limited to life and health but also in terms of physical and intellectual function as well as morale of those affected. The objective of the study was to assess the fire safety provisions of hostels and factors associated with level of knowledge, attitude and practices (KAP) in fire safety and prevention among students (hostel’s occupant) in Universiti Putra Malaysia’s (UPM) residential colleges. A cross-sectional study conducted at UPM’s residential colleges from March 2020 to October 2020. An adapted checklist which was cross-referenced to Uniform Building By-Laws (UBBL) was used to determine the compliance of fire safety provision of the residential buildings. In term of fire safety provision, all colleges were included, and a checklist was used in the research to collect data by observation which was done by researcher with help from the management staff. Convenient sampling was used to collect KAP on fire safety by online questionnaire from students. Face validity, content validity, and reliability value of KAP questionnaire were checked. Multiple logistic regression was used to investigate factors associated with KAP on fire safety among students. A total of 283 students took part in the study, and 8 residential colleges were assessed in term of fire safety provision. Assessment using checklist revealed that despite available fire safety policy at all residential colleges, there were differences and inadequacy in terms of fire safety provision which may be attributable to the different management and operational team. Specifically, there were no uniformity in terms of investigated provisions (and aspects); prevention of fire occurrence (control of ignition sources, fuel/heat interaction and fuel characteristics), control spread of fire (fire detection and combustion control) as well as protection of building occupants (notification, egress and structural protection) across all residential colleges. Prevalence of having acceptable knowledge, positive attitude and good practices was 62.0%, 87.9% and 49.3% respectively. Multiple logistic regression indicated that non-Malay students, experiences in fire drill training and hands-on experiences in fire drill training were significantly associated with knowledge. However, only hands-on in fire drill training was significantly associated with attitude (OR= 2.285, 95%CI: 1.048, 4.980, p = 0.038) while total household monthly income of RM4,850-RM10,959 was significantly associated with practices (OR= 3.000, 95%CI: 1.181, 7.620, p = 0.021). Based on findings in this study, there are dire need to address not only the nonuniformity and inadequacy of fire safety provision across different residential colleges, but also take into consideration the level of fire safety KAP among students and its associated factors, to identify the potential risks and developing programs to enhance fire safety KAP.